Effect of Various Phases of Menstrual Cycle on Autonomic Reactivity to Emotional and Cognitive Stressors - Shalini Gupta; Ashi Junaniya; Avani Ahuja; Radha Anjana (Journal of Pharmacy and Bioallied Sciences)
Background: Researching how women’s emotional, cognitive, and cardiovascular changes relate to cyclic changes and its correlation with various stages of the menstrual cycle is crucial. Aim: To assess the effect of various phases of the menstrual cycle on autonomic reactivity to emotional and cognitive stressors. Methods: The present study assessed 124 eumenorrheic females in the age range of 18–20 years, where emotional and cognitive stressors were assessed as emotional Stroop test and PASAT that was conducted on the 10th day and 20th day of the menstrual cycle depicting the follicular and luteal day after determining phases with prism calendar and basal body temperature. DBP, SBP, and HR were assessed at baseline and following stressors. The results were compared in two phases. Results: At baseline, DBP, SBP, and HR were higher in the luteal phase compared to the follicular phase. PASAT showed that HR recovery was 3.30 min and 4.10 min in the follicular and luteal phases, respectively. SBP recovery was 2.20 min and 2.50 min in the follicular and luteal phases, respectively. DBP recovery was 1.40 min and 2.10 min in the follicular and luteal phases, respectively. In the emotional Stroop test positive, word latency was 1256.435 and 1034.52 ms in the follicular and luteal phases, respectively. Negative word latency was 1145.784 and 1335.302 ms in the follicular and luteal phases, respectively. Conclusions: The luteal phase presents higher SNS reactivity and thus, emotional and cognitive stressors gather more sympathetic activity; finally, a definitive interaction is seen in the gonadal hormones and higher cognitive centers of female subjects.